(untitled) (Research, Society and Development, 2021)
In modern medicine, the use of plants for therapeutic purposes is called phytotherapy and its use is increasing among the general population, researchers and health professionals. One of the popular applications is the use of infusions for nephrological alterations, especially in the formation of calculi, or even kidney stones. Thus, in view of the great popular use of infusions, this work aims to evaluate the toxicity and hydrogenic infusion potential of the stem of Equisetum arvense L. (Horsetail), flowers of Hibiscus sabdariffa (Hibiscus) and leaves of Persea americana (avocado). For experimental evaluation, samples of natural products were obtained commercially and the preparation of infusions was added to water and heated to a boiling point. For toxicity testing, 300 µL of the infusion was added to a 96-well culture plate at room temperature and one seed per well of Allium cepa was inoculated. of a peagometer, measurements of the pH value were carried out for 96 hours. No changes in germination and growth were identified in the tested infusions. As for the hydrogenic potential, the infusion of Horsetail (E. arvense) showed acidification of the medium by 10%, while Hibiscus (H. sabdariffa) had 64% acidification and the avocado leaves had 21% acidification. Based on what has been demonstrated, the consumption of infusions of Horsetail, Hibiscus flowers and Avocado leaves proved to be safe against the Allium cepa test and promising for the treatment of alkaline urolithiasis, in addition to the antioxidant effects present in the literature. However, it can be harmful in cases of acid urolithiasis formation.